Microstructures, Heat Treatment, and Properties of Boron‐Alloyed Tool Steels. Issue 5 (4th December 2019) - Lentz, Jonathan; Röttger, Arne; Theisen, Werner
Abstract : To enable the development of novel Fe–C–B–Cr and Fe–C–B–Cr–Mo cold work tool steels, the microstructures and hardness‐tempering behaviors of hypoeutectic laboratory melts are investigated. The results show that increasing Cr content enhances the thermodynamic stability of the ultrahard M2 B borides. The formation of carboborides is suppressed by adjusting the B/(C + B) ratio, Cr content, and austenitization temperature. A secondary hardenability at 500 °C is achieved by Mo addition. In addition, Mo stabilizes the M23 (C, B)6 phase and at higher contents the M3 B2 boride. Based on these investigations, Fe0.4C1B–Cr alloys are designed which, inspired by the microstructure of the steel X153CrMoV12‐1, feature a α′‐Fe hardenable matrix but 15 vol% of eutectic M2 B borides instead of M7 C3 for wear protection. The Fe0.4C1B–Cr steels are produced by casting and hot rolling as well as powder metallurgy and hot isostatic pressing. The (tribo‐) mechanical properties are investigated and compared with X153CrMoV12‐1. Fracture toughness, bending strength, wear resistance, and hardness of the novel Fe0.4C1B–Cr alloys are found to be similar or superior to the steel X153CrMoV12‐1, at decreased material cost. Abstract : The microstructures of novel Fe–C–B–Cr and Fe–C–B–Cr–Mo cold work tool steels are characterized. In addition, the (tribo‐) mechanical properties are investigated and compared with the steel X153CrMoV12‐1. Fracture toughness, bending strength, wear resistance, and hardness of the novel Fe0.4C1B–Cr alloys are found to be similar or superior to the steel X153CrMoV12‐1, at decreased material cost.